Pengaruh Penerapan Good Corporate Governance dan Corporate Social Responsibility terhadap Kinerja Keuangan Perusahaan: Studi Empiris pada Perusahan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 - Fathiyyah, Fathiyyah; Taqwa, Salma (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to analyze the effect of corporate financial performance in relation to good corporate governance, which includes managerial ownership, independent commissioners, the board of directors, and corporate social responsibility. The research object is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The sample was obtained using a purposive sampling method, resulting in 201 observations over the three-year research period. Data were analyzed using panel data regression with the E-Views software. The findings indicate that managerial ownership has no significant effect, independent commissioners have a positive and significant effect, the board of directors has no significant effect, and corporate social responsibility has a positive and significant effect on corporate financial performance.